EKSKLUSIFITAS SISWA (STUDI FENOMENOLOGI KONSTRUKSI SOSIAL POLA EKSKLUSIFITAS SISWA PADA KELAS UNGGULAN DI SMA MUHAMMADIYAH 1 SRAGEN TAHUN AJARAN 2011/2012) - Rita Indawatik; Drajat Tri Kartono; Trisni Utami (Jurnal Analisa Sosiologi, 2013)
Superior class (school) is designed to provide adequate learning service to the students with high academic competency. Consequently, this strategy cannot support the attempt of optimizing the rapid development of human resource. On the other hand, the superior class phenomenon also gives rise to exclusive behavior in which the students tend to make group and have intercourse with their superior classmates only. It is that makes the author interested in finding out how the exclusiveness pattern of behavior emerges in the superior students.The research strategy employed was phenomenological study. The respondent was selected using purposive sampling technique considering the compatibility between information and the problem studied. This study was based on constructivism paradigm under the heading of Social Definition paradigm. This Peter L. Berger’s constructivism idea stated that in constructivism idea, learning was based on the students’ understanding.The exclusiveness behavioral pattern in the superior students occurred in thought, appearance, space, facility pattern and intercourse. Meanwhile, the process of exclusiveness process establishment occurred since they were stated as passing the admission test in superior class. The factors supporting the establishment of exclusiveness pattern were school policy, parent and student because of the process of interpreting their status as the students of superior class. Keywords: social construction, exclusiveness, superior students.